Pelaksanaan Metode POAC Sebagai Strategi Manajemen Bisnis Kursus Pada LPK NURLITA Bandung - Budi Lesmana (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2020)
This research is to aims the determine of POAC Management Strategy toward quality of services in LPK Nurlita Bandung. The sample in this research were 50 respondents as a LPK Nurlita customer who visit more than 2x, by using sampling technique is a tecnique for determining quota sample of the population that have certain character that are used by researchers. Data analysis technique used is a sample linear regression. The results showed that the quality of services and significant positif satisfaction in LPK Nurlita Bandung.